Upaya Meningkatkan Kemampuan Mengenal Konsep Warna Melalui Kegiatan Meronce Pada Anak Kelompok B TK Dharma Wanita 2 Mojotengah Kedu Temanggung Semester I Tahun Pelajaran 2017/2018 - Tri Miyasih (Universitas PGRI Semarang, 2020)
One of the basic competencies in kindergarten is that children can recognize simple concepts with indicators that children are able to recognize color concepts. Color recognition for children can stimulate the senses of sight, brain, aesthetics, and emotions. Meronce activities are aimed at training children's eye and hand coordination. The rationale for this problem arises is the low ability to recognize the concept of color in Group B TK Dharma Wanita 2 Mojotengah. The purpose of this study was to determine the process of meronce activities to improve the ability to recognize children's color concepts and to determine the magnitude of the increase in the ability to recognize color concepts after resonating activities in Group B children TK Dharma Wanita 2 Mojotengah Kedu Temanggung Semester I Academic Year 2017/2018. The subjects of this study were 15 students of Group B TK Dharma Wanita 2 Mojotengah. The research was carried out from September to October 2017. The data collection methods used were observation, documentation, and interviews. Based on the results of research and discussion, it can be concluded that meronce activities can improve the ability to recognize color concepts in Group B children TK Dharma Wanita Mojotengah 2. This can be seen from the results of increasing the ability to recognize color concepts in Group B children TK Dharma Wanita Mojotengah 2 in The pre-cycle condition was 20% then increased to 46.7% in Cycle I and finally increased in Cycle II by 93.3%, it was proven that the child was able to designate colors, mention or differentiate colors and classify colors.